PENGARUH VOLATILITAS ARUS KAS, VOLATILITAS PENJUALAN, LEVERAGE, DAN BOOK TAX DIFFERENCES TERHADAP PERSISTENSI LABA - Ariyanti, Rizka; Imron, Ali; Aditya, Dicky (Politeknik Negeri Semarang, 2024)
This study aims to determine the effect of cash flow volatility, sales volaticity, leverage, and book tax differences in 2017-2021. Quality profit is persistent profit, that is, profit that is sustainable, more permanent, and not temporary. The type of data used is secondary data of propery and real estate companies obtained from the Indonesia Stock Exchange (IDX). This research uses the method The sampling technique used was purposive sampling technique with a population of 87 companies with a sample of 9 companies. The data analysis method used is quantitative data analysis, which uses panel data regression analysis with the Eviews 10 application program. The partial results show that cash flow volatility has no effect on profit persistence, sales volatility has a negative and significant effect on profit persistence, Laverage has no effect on profit persistence and Book tax differences have a significant positive effect on profit persistence, and simultaneously shows that cash flow volatility, sales volatility, leverage and book tax differences, have a significant effect simultaneously on profit persistence with R2 of 76%.